Ethnomathematics exploration of fisherman activities in the Rembang community - Muna, Faizul; Fuadi , Muhammad Hilman; Nurhuda, Abid (Nusantara Journal of Behavioral and Social Science, 2023)
Mathematics is a science that cannot be separated from human life. It is also applied in various aspects of daily life, one of which is in the activities of fishermen in the Rembang community. And the purpose of this study is to describe the Ethnomathematics Exploration in the Activities of Fishermen of the Rembang Community. The method used is field qualitative, then relevant data is collected and analyzed, and finally concluded descriptively. The results showed that ethnomathematics activities in the fishing activities of the Rembang community included measuring the vessel to determine its type by multiplying the decimal number, as well as buying and selling activities in the market which involved addition and subtraction. Abstrak: Matematika merupakan salah satu ilmu yang tidak bisa lepas dari kehidupan manusia. Bahkan ia juga diaplikasikan dalam berbagai aspek dalam keseharian salah satunya adalah pada kegiatan nelayan di masyarakat rembang. Dan tujuan dari penelitian ini adalah untuk mendeksripsikan terkait Eksplorasi Etnomatematika Pada Kegiatan Nelayan Masyarakat Rembang. Metode yang digunakan adalah kualitatif lapangan, lalu dikumpulkan data yang relevan serta dianalisis dan terakhir disimpulkan secara deksriptif. Hasil penelitian menunjukkan bahwa aktivitas etnomatematika pada kegiatan nelayan masyarakat Rembang mencakup pengukuran kapal untuk menentukan jenisnya dengan prosedur perkalian pada bilangan decimal, serta kegiatan jual beli hasil tangkapan dipasar yang melibatkan penjumlahan dan pengurangan.